2018
DOI: 10.1016/j.cell.2018.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Structures of DPAGT1 Explain Glycosylation Disease Mechanisms and Advance TB Antibiotic Design

Abstract: SummaryProtein N-glycosylation is a widespread post-translational modification. The first committed step in this process is catalysed by dolichyl-phosphate N-acetylglucosamine-phosphotransferase DPAGT1 (GPT/E.C. 2.7.8.15). Missense DPAGT1 variants cause congenital myasthenic syndrome and disorders of glycosylation. In addition, naturally-occurring bactericidal nucleoside analogues such as tunicamycin are toxic to eukaryotes due to DPAGT1 inhibition, preventing their clinical use. Our structures of DPAGT1 with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 53 publications
2
90
0
Order By: Relevance
“…Tunicamycin is the only non-selective nucleoside inhibitor among the five known classes, with off-target effects on the human MraY paralog, GPT. GPT lacks a binding pocket analogous to the uridine-adjacent pocket in MraY 14,15 . Therefore, targeting the uridine-adjacent pocket could be a strategy to engineer selectivity of nucleoside inhibitors for MraY over GPT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tunicamycin is the only non-selective nucleoside inhibitor among the five known classes, with off-target effects on the human MraY paralog, GPT. GPT lacks a binding pocket analogous to the uridine-adjacent pocket in MraY 14,15 . Therefore, targeting the uridine-adjacent pocket could be a strategy to engineer selectivity of nucleoside inhibitors for MraY over GPT.…”
Section: Resultsmentioning
confidence: 99%
“…Recent structures of tunicamycin bound to MraY 13 and GPT 14,15 show that the tunicamycin binding pocket is deep and occluded in GPT, while in MraY it is shallow and largely exposed to the cytosol. The MraY inhibitor binding site on the cytoplasmic face of MraY is unlike the large, deep, and enclosed binding pockets typically found in enzyme active sites 16 .…”
Section: Introductionmentioning
confidence: 99%
“…12 Given the qualitative nature of these experiments, we chose to use Gram-positive lipid II, which we previously prepared by total chemical synthesis. 28 Oct-TriA 2 (9 -N MePhe) ( 15 ), Oct-TriA 2 (6-Sar) ( 20 ), and Oct-TriA 2 (6-Sar, 9 -N MePhe) ( 22 ) were incubated with an excess (7 equiv) of lipid II for 30 min, before being applied to a freshly prepared agar plate that had been inoculated with E. coli and incubated for 18 h at 37 °C. Whereas a clear zone of inhibition was observed for each peptide when no lipid II is present, the addition of lipid II sequesters antimicrobial activity, showing that synthetic tridecaptin analogues 15 , 20 , and 22 retain lipid II binding.…”
Section: Resultsmentioning
confidence: 99%
“…Tunicamycins are a group of nucleoside antibiotics that act as reversible inhibitors of translocase I in bacterial peptidoglycan biosynthesis and inhibit protein glycosylation in eukaryotic cells. Very recently, it has been shown that tunicamycins can be interesting scaffolds for the development of new antibiotics against tuberculosis (Dong et al, 2018). S. clavuligerus has been described as a producer of tunicamycins (Kenig and Reading, 1979) and PimM expression leads to a fivefold increase in tunicamycin production.…”
Section: Discussionmentioning
confidence: 99%